Respuesta :

Simplifying -12x + 14 = -34 + -12x + 14 + -34 Reorder the terms: 14 + -12x = -34 + -12x + 14 + -34 Reorder the terms: 14 + -12x = -34 + 14 + -34 + -12x Combine like terms: -34 + 14 = -20 14 + -12x = -20 + -34 + -12x Combine like terms: -20 + -34 = -54 14 + -12x = -54 + -12x Add '12x' to each side of the equation. 14 + -12x + 12x = -54 + -12x + 12x Combine like terms: -12x + 12x = 0 14 + 0 = -54 + -12x + 12x 14 = -54 + -12x + 12x Combine like terms: -12x + 12x = 0 14 = -54 + 04 = -54 Solving 4,

In short responce,I'm sorry I took forever,this was hard,Your answer is C,x=4